2019
DOI: 10.1016/j.plefa.2019.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of blue mussel (Mytilus edulis) intake on fatty acid composition in erythrocytes and plasma phospholipids and serum metabolites in women with rheumatoid arthritis

Abstract: Running title: Influence of blue mussels on fatty acids and metabolites Funding: The MIRA study was supported by Hakansson Foundation (2014) and The Swedish government under the ALF-funds (an agreement between healthcare and research) (Grant Number ALFGBG-716341). The companies Gron Ko, Mat.se, Coldcargo AB and Vilsund Blue AB reduced their prices to aid the study meal production and delivery. Analysis in the presented work was funded by IRIS-scholarship (2016) and Langmanska Cultural Fund (BA17-2 0928). None … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Another study in an RA Swedish population found that EPA and DHA were both increased in erythrocytes after a blue mussel diet compared to a control diet, resulting in a decrease of n-6 PUFA ARA (20:4 n-6) and dihomo-gamma-linolenic acid (DGLA; 20:3 n−6), as well as a small decrease in saturated fatty acids and the monounsaturated fatty acid palmitoleic acid (16:1 n-7). Baseline EPA and DHA levels in this population were higher than in healthy men and women, but this group had of 31 already reported that the RA population from the studied area had a higher fish and shellfish intake compared to the general population of Sweden [211]. In contrast to these findings, erythrocyte levels of α-linolenic acid (ALA; 18:3n3), EPA 20:5n3, and the omega-3 index (EPA plus DHA) were found to be significantly lower in RA patients compared to healthy controls in a Korean population, although diet was not accounted for in this study.…”
Section: Studies Of Beneficial Effect Of Diet In Ramentioning
confidence: 57%
“…Another study in an RA Swedish population found that EPA and DHA were both increased in erythrocytes after a blue mussel diet compared to a control diet, resulting in a decrease of n-6 PUFA ARA (20:4 n-6) and dihomo-gamma-linolenic acid (DGLA; 20:3 n−6), as well as a small decrease in saturated fatty acids and the monounsaturated fatty acid palmitoleic acid (16:1 n-7). Baseline EPA and DHA levels in this population were higher than in healthy men and women, but this group had of 31 already reported that the RA population from the studied area had a higher fish and shellfish intake compared to the general population of Sweden [211]. In contrast to these findings, erythrocyte levels of α-linolenic acid (ALA; 18:3n3), EPA 20:5n3, and the omega-3 index (EPA plus DHA) were found to be significantly lower in RA patients compared to healthy controls in a Korean population, although diet was not accounted for in this study.…”
Section: Studies Of Beneficial Effect Of Diet In Ramentioning
confidence: 57%
“…We have previously presented findings showing that patterns of erythrocyte fatty acids could predict all individuals’ dietary periods (mussel intervention vs. control diet) correctly in an OPLS-EP model [ 21 ], but this was not possible for oxylipins. Neither OPLS-EP nor OPLS-DA resulted in models of high quality with a good predictability ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fasting blood samples were collected before and after each dietary period and were analyzed for free fatty acids and oxylipins in erythrocytes. Erythrocyte fatty acid concentrations have been reported previously [ 21 ]. Figure 3 describes the relationship between the presented lipids (total fatty acids, free fatty acids, and oxylipins) in erythrocytes in this paper and their products.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Lindqvist [ 18 ], patients on a blue mussel diet had lower CRP, fewer tender joints, significantly improved global health and reduced pain and fatigue. In another study by Lindqvist [ 17 ], changes in the increase of omega-3 FAs EPA and DHA were observed in a group of patients who consumed blue mussels. In a study by Barebring et al [ 65 ], a diet rich in fish, crustaceans, fruit and vegetables and whole grains was associated with a reduction in ESR (B = −2.4, p = 0.002) and hs-CRP (B = −0.6, p = 0.044).…”
Section: The Role Of Fatty Acids In the Treatment Of Ramentioning
confidence: 99%